Effect of temperature and substrate on germination of Peltophorum dubium (Sprengel) Taubert seeds - doi: 10.4025/actascibiolsci.v33i1.7057 - Alves, Edna Ursulino; Guedes, Roberta Sales; Gonçalves, Edilma Pereira; Viana, Jeandson Silva; Santos, Sueli da Silva; Moura, Mácio Faria de (Acta Scientiarum. Biological Sciences, 2011)
Peltophorum dubium (Spreng.) Taub. is a species belonging to the family Fabaceae, and is known popularly as golden shower tree. Its wood has multiple uses in reforestation programs and as an ornamental tree, and is also considered an endangered species, requiring studies that assist in its preservation. The present work was conducted with the objective of determine the ideal substrate type and temperature to perform germination and vigor tests with P. dubium seeds. The experiment was carried out at the Seed Analysis Laboratory (Centro de Ciências Agrárias, Universidade Federal Paraíba, Areia, Paraíba, Brazil), in a completely randomized design. The treatments were distributed in a 4 x 6 factorial scheme; temperatures (constant temperatures of 25, 30 and 35°C; and alternate temperatures of 20-30°C) and substrate (paper towel, over blotting paper, in sand, in vermiculite, Bioplant® and Plantmax®) on four replications of 25 seeds. The following parameters were analyzed: germination percentage, germination speed index, first germination count, length and dry mass of seedlings. The constant temperature of 30°C and 20-30°C alternate, and the substrates into sand and paper towel can be recommended for germination and vigor tests of P. dubium seeds. The temperature of 25°C should not be used in germination and vigor tests of P. dubium seeds in any of the tested substrates.